'Ripples': message-efficient, coverage-aware clustering in wireless sensor and actor networks. (1st December 2008) - Trivedi, Neeta; Iyengar, S. Sitharama; Balakrishnan, N.
We propose 'ripples', a lightweight scalable algorithm for self-organisation and self-healing in wireless sensor and actor networks (WSAN). The novelty of the algorithm lies in its unified approach to deterministically address the multitude of challenges present in WSAN with extremely low communication and computation overheads, optimally exploiting the redundant deployment. 'Ripples' also facilitates design of efficient data dissemination algorithms and networking protocols for routing with guaranteed delays. A sub-module 'bind' has been outlined that associates the clusters to their nearest actor nodes; this is required for real-time response. 'Bind' works along with 'ripples' and creates route and data tables that can be used by the data dissemination algorithm and networking protocols for efficient operation.